2011
DOI: 10.1097/aog.0b013e31821b5118
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multivariate Index Assay in the Preoperative Assessment of Ovarian Tumors

Abstract: The multivariate index assay demonstrated higher sensitivity and lower specificity compared with physician assessment and CA 125 in detecting ovarian malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
173
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(185 citation statements)
references
References 26 publications
4
173
1
7
Order By: Relevance
“…These findings thus add confidence to the discovery and partly support the validity of the markers used in the Ova1 test. Whilst the performance of the non‐CA125 Ova1 markers without CA125 has not been evaluated directly, one study showed that the Ova1 test detected over 50% of malignancies missed by CA125 alone 28. Without inclusion of physician's assessment, the sensitivity and specificity of CA125 alone (cut‐off 35 U/mL) were 77 and 73%, respectively, versus 93 and 43% using the Ova1 test.…”
Section: Discussionmentioning
confidence: 99%
“…These findings thus add confidence to the discovery and partly support the validity of the markers used in the Ova1 test. Whilst the performance of the non‐CA125 Ova1 markers without CA125 has not been evaluated directly, one study showed that the Ova1 test detected over 50% of malignancies missed by CA125 alone 28. Without inclusion of physician's assessment, the sensitivity and specificity of CA125 alone (cut‐off 35 U/mL) were 77 and 73%, respectively, versus 93 and 43% using the Ova1 test.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A total of 1110 subjects were prospectively enrolled at 44 sites across the United States, including primary care women's health clinics, general obstetrics and gynecology group practices, gynecologic oncology practices, community and universitybased hospitals, and health maintenance organizations. Institutional review board approval was obtained from each site.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 Biomarker measurements were performed according to the MIA Instructions for Use at Quest Diagnostics, Inc (Chantilly, VA) or the Division of Clinical Chemistry, Department of Pathology, Johns Hopkins Medical Institutions. The MIA is a FDAcleared, assay that incorporates CA125 (CA125-II), transferrin, transthyretin (prealbumin), apolipoprotein A1, and beta-2-microglobulin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations